Explaining genocide and the question of theory - Van Zyl, Susan (PINS-Psychology in Society, 2024)
One of the most surprising things about Sabby Sagall’s Final solutions: Human nature, capitalism and genocide is the fact that it was published in 2013. Perhaps because of the “post-theory condition” in which most people work today, had I been asked to guess the year of its publication based on the title alone, I would have suggested that it was written in the mid to late seventies – before an unselfconscious engagement with the very idea of a theoretical synthesis between Freud and Marxist, in traditional form at least, became virtually unthinkable. But on reading Final solutions I discovered that the work took the form of just that, of an unselfconscious – neither Anti-Oedipus (1983) nor anything on late or post capitalism is in the bibliography – attempt to give equal weight to Marx and Freud in generating a theory of genocide. This theory, given the presence of psychoanalysis and historical materialism must, and explicitly does, attempt to make one of the most challenging of all close connections, that between the psyche and the social, and not just in a particular case but in such a way as to sustain a theory applicable to more than one genocide.